On the taxonomic status of Bufo brasiliensis Laurenti, 1768 - Valencia-Zuleta, Alejandro; Caramaschi, Ulisses; Maciel, Natan M. (Zootaxa, 2018)
The name Bufo brasiliensis was proposed by Laurenti (1768) and, for a long time, has been associated with the widely distributed Marine toad - Rhinella marina (Linnaeus, 1758). However, we found several inconsistences in this taxonomic proposal and disagree with it. We argue that the specimen illustrated does not correspond to any bufonid form (even less the Neotropical genus Rhinella) based on the following argumentation presented below. Laurenti (1768) used Seba’s (1734) illustration in plate 73 (Fig. 1) to establish the name B. brasiliensis.